2009
DOI: 10.1042/cs20090035
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 promoter haplotypes confer an increased risk of stroke in a Chinese Han population

Abstract: Angiopoietin-2 is an important mediator of angiogenesis, and we hypothesized that genetic variants of ANGPT2 (the gene encoding angiopoietin-2) would result in abnormal angiogenesis and contribute to stroke susceptibility. To test our hypothesis, we investigated the association of variants in the promoter of ANGPT2 with stroke in a multi-centre case-control study. We found that the C allele of rs3739390 conferred a 1.42-fold risk of lacunar infarction {adjusted OR (odds ratio), 1.42 [95% CI (confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…These findings thus provide new evidence suggesting the importance of ANGPT2 in psoriasis susceptibility. Regarding the functional effect of the ANGPT2 polymorphism, it has been reported that the ANGPT2 polymorphisms rs2442598 and rs1868554 are strongly associated with the development of acute lung injury in patients after major trauma, and further evidence indicates that rs3739390 is associated with a high risk of stroke in the Chinese population . However, in the current study, we did not find any association between PV and either rs1868554 or rs3739390.…”
Section: Discussioncontrasting
confidence: 91%
“…These findings thus provide new evidence suggesting the importance of ANGPT2 in psoriasis susceptibility. Regarding the functional effect of the ANGPT2 polymorphism, it has been reported that the ANGPT2 polymorphisms rs2442598 and rs1868554 are strongly associated with the development of acute lung injury in patients after major trauma, and further evidence indicates that rs3739390 is associated with a high risk of stroke in the Chinese population . However, in the current study, we did not find any association between PV and either rs1868554 or rs3739390.…”
Section: Discussioncontrasting
confidence: 91%
“…Angpt2 was considered as a proangiogenic factor that could be responsible for endothelial dysfunction and increased risk for vascular disorders [ 29 ] and functioned as a biomarker to predict the life expectancy of peripheral arterial disease patients [ 30 ]. A multi-center case–control study on stroke patients further showed the association of variants in the promoter of Angpt2 with stroke [ 31 ]. A knockout mice study also demonstrated that treatment of Angpt2-neutralizing antibody attenuated the defects in vascular malformations, which shows that Angpt2 can be used for treatment and is not only important as a biomarker [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to SLE patients, recent data from Wang et al showed that patients carrying ANGPT2 rs3739390 G allele were more likely to develop symptoms of hematuria and hypocomplementemia, and GC genotype frequency of rs3739390 was higher in patients with ds-DNA (+) that is associated with more severe variants of the disease [29]. In contrast, in patients with stroke, the G allele of ANGPT2 rs3739390 conferred a lower risk of lacunar infarction than the corresponding allele C [32].…”
Section: Discussionmentioning
confidence: 99%
“…Given that Ang1/Ang2 serum concentrations are known to be altered in SSc patients, and that some ANGPT1 and ANGPT2 SNPs seem to affect their levels in other pathological conditions [28,32,40,41], we additionally explored the possible effect of analyzed ANGPT1 and ANGPT2 genetic variants on their corresponding proteins in serum of SSc subjects. Serum Ang2 levels were significantly increased in SSc cases in contrast to HCs and vary substantially by ANGPT2 rs3739390 genotype.…”
Section: Discussionmentioning
confidence: 99%